The effect of attitude and understanding towards goods and service tax satisfaction among business community in Malaysia - Abdul Aziz, Saliza; Bidin, Zainol; Marimuthu, Munusamy (American Scientific Publishers, 2017)
The Malaysian business communities especially the owners/managers of manufacturing companies in Malaysia are concerned that Goods and Service Tax (GST) would adversely affect their business. The decision to implement GST was made by the government after the tax review panel for GST received numerous feedbacks from the public and business community appealing for an extension of time in implementing GST. The desire state is that taxpayers need to be positive in attitude and well understand of what GST is about for voluntarily compliance. As such gaps exist between the desired state and the actual state with regards to acceptance/satisfaction of GST in this country by business community could improve the compliance rate indirectly. The main objective of this study is to gain understanding on the gaps existed in achieving the satisfaction among the Malaysian business communities. In seeking for the imperative answers, this research is design for the following objectives (1) to identify the level of attitude and understanding toward GST implementation satisfaction; and (2) to determine the relationship between attitude and understanding with satisfaction towards GST implementation in Malaysia. Via the Regression method, it is revealed and supported that attitude and understanding are the significant paths in influencing the satisfaction towards GST implementation in Malaysia among the business communities.